Benign incidental findings of osteopoikilosis on Tc-99m MDP bone SPECT/CT: A case report and literature review - Tsai, Szu-Ying (Medicine (Baltimore), 2016)
Osteopoikilosis is a benign but rare condition characterized by bone islands throughout the osseous tissue, which could be easily confused with bone metastasis. We present a case of a 37-year-old man presented to orthopedic outpatient clinic with right hip pain for 2 weeks. There were multiple, small punctate lesions scattered throughout the skeleton on radiograph. Subsequent Tc-99m methylene diphosphonate (MDP) bone scan with pelvic single-photon emission computed tomography (SPECT)/computed tomography (CT) showed multiple enostoses without abnormal focal MDP uptake. Therefore, clinical diagnosis was compatible with osteopoikilosis while bone metastasis was unlikely. The symptoms then improved by conservative treatments. Osteopoikilosis is usually an incidental finding on radiograph or CT, and a normal MDP confirmed the diagnosis by excluding bone metastasis. It is important for clinicians to recognize the specific image features to prevent further unnecessary interventions. In addition, bone SPECT/CT could also make the diagnosis in one step.